Surface and proton conductivity properties of electrospun poly(vinyl butyral)/polyaniline nanofibers - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (WILEY, 2018)
Proton-conductive electrospun nanofibers are promising potential materials for several advanced technological applications such batteries, sensors, and fuel cells. In this work, we prepared poly(vinyl butyral)/polyaniline (PVB/PANI) nanofibers via electrospinning and determined their proton conductivities. Structural characterization of the nanofibers was performed by FTIR analysis. Surface morphology of the nanofibers was determined by SEM and AFM. The addition of PANI significantly affected the fiber morphology, and over 90% reduction (with respect to neat PVB nanofibers) in the average nanofiber diameters was observed. Nanofiber mats were doped with polyphosphoric acid. The proton conductivity of the 2 wt.% PANI containing blend nanofibers was found as 18 x 10(-6) S/cm at room temperature and at 100% humidity.
Keywords: atomic force microscopy; electrospinning; poly(vinyl butyral); polyaniline; proton conductivity; POLYVINYL-ALCOHOL; AQUEOUS-SOLUTIONS; POLYANILINE; MEMBRANES; HUMIDITY; FIBERS; FILMS; PANI